Tn-Seq Analysis Identifies Genes Important for Yersinia pestis Adherence during Primary Pneumonic Plague - Kara R. Eichelberger; Victoria E. Sepúlveda; John Ford; Sara R. Selitsky; Piotr A. Mieczkowski; Joel S. Parker; William E. Goldman (mSphere, 2020)
ABSTRACT Following inhalation, Yersinia pestis rapidly colonizes the lung to establish infection during primary pneumonic plague. Although several adhesins have been identified in Yersinia spp., the factors mediating early Y. pestis adherence in the lung remain unknown. To identify genes important for Y. pestis adherence during primary pneumonic plague, we used transposon insertion sequencing (Tn-seq). Wild-type and capsule mutant (Δcaf1) Y. pestis transposon mutant libraries were serially passaged in vivo to enrich for nonadherent mutants in the lung using a mouse model of primary pneumonic plague. Sequencing of the passaged libraries revealed six mutants that were significantly enriched in both the wild-type and Δcaf1 Y. pestis backgrounds. The enriched mutants had insertions in genes that encode transcriptional regulators, chaperones, an endoribonuclease, and YPO3903, a hypothetical protein. Using single-strain infections and a transcriptional analysis, we identified a significant role for YPO3903 in Y. pestis adherence in the lung and showed that YPO3903 regulated transcript levels of psaA, which encodes a fimbria previously implicated in Y. pestis adherence in vitro. Deletion of psaA had a minor effect on Y. pestis adherence in the lung, suggesting that YPO3903 regulates other adhesins in addition to psaA. By enriching for mutations in genes that regulate the expression or assembly of multiple genes or proteins, we obtained screen results indicating that there may be not just one dominant adhesin but rather several factors that contribute to early Y. pestis adherence during primary pneumonic plague. IMPORTANCE Colonization of the lung by Yersinia pestis is a critical first step in establishing infection during primary pneumonic plague, a disease characterized by high lethality. However, the mechanisms by which Y. pestis adheres in the lung after inhalation remain elusive. Here, we used Tn-seq to identify Y. pestis genes important for adherence early during primary pneumonic plague. Our mutant enrichment strategy resulted in the identification of genes important for regulation and assembly of genes and proteins rather than adhesin genes themselves. These results reveal that there may be multiple Y. pestis adhesins or redundancy among adhesins. Identifying the adhesins regulated by the genes identified in our enrichment screen may reveal novel therapeutic targets for preventing Y. pestis adherence and the subsequent development of pneumonic plague.